D-dimer Analysis in COVID-19 Patients - Abd. Rahim Mubarak; Tenri Esa; Yuyun Widaningsih; Uleng Bahrun (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
The COVID-19 incidence is increasing around the world. Some countries are experiencing worsening conditions, even deaths. One coagulation marker that noticeably increases in COVID-19 patients is D-dimer. This study aimed to analyze D-dimer levels of COVID-19 patients. Retrospective study using medical records of 84 COVID-19 patients, conducted from April to August 2020 at UNHAS Hospital. Patients were grouped based on the severity of the disease as non-severe and severe. D-dimer levels were measured using the Alere Triage® D-dimer with the fluorescent immunoassay method. The statistical test used was Mann-Whitney, D-dimer prognostic levels were calculated with ROC analysis to get the cut-off. Significant if the p < of 0.05. The sample consisted of 74 non-severe and ten severe COVID-19 patients, mostly in the 30-39 age group. D-dimer levels in non-severe (0.31±0.38 Î¼g/L) significantly differ from severe group (3.09±2.56 Î¼g/L) (p<0.001). The Receiver Operating Characteristics (ROC) curve showed D-dimer sensitivity and specificity of 90.0% and 89.2%, respectively at the â‰¥ 0.80 Î¼g/L cut-off, Negative Predictive Value (NPV) of 98.5%, and Positive Predictive Value (PPV) of 52.9%. D-dimer levels increased in severe COVID-19 patients due to an increased inflammatory response resulting in excessive thrombin. The ROC D-dimer curve indicated a cut-off rate of 0.80 Î¼g/L, providing optimal sensitivity and specificity. D-dimer has a significant difference in non-severe and severe COVID-19 patients and shows good value to determine the severity of COVID-19 disease with a cut-off value â‰¥ 0.80 Î¼g /L.